Investigation into the Impact of Groove Shape on the Tensile Strength of Commercial Steel - Elfallah, Saleh (International Journal of Integrated Engineering, 2024)
In industry, welding is well known. There is a great demand for effective and quality welding. Manufacturers seek to remain competitive in the market. They rely on their manufacturing engineers and production personnel to quickly and effectively set up manufacturing processes for new products. GMAW is one of the most widely used processes in the industry. Input factors such as welding current, welding voltage, Gas flow rate, wire feed speed (WFS), wire size and welding speed play a significant role in determining the welding quality. Taguchi's design has been a powerful and efficient optimization tool for better quality and performance output of manufacturing processes. In this study, GMAW has welded commercial steel under preset factors of welding voltage, WFS and groove shape. X groove weldments obtained lower tensile strength and hardness than V groove weldments. Taguchi's design is to determine the optimal process factors for higher tensile strength and hardness. The analysis found that welding groove shape had the highest effect on tensile strength and hardness of the welding, followed by voltage. WFS had the lowest influence on tensile strength and hardness. The optimized combination of welding factors is V groove shape, 20 V and 5.9 m/min WFS.